The E-Id Axis Instructs Adaptive Versus Innate Lineage Cell Fate Choice and Instructs Regulatory T Cell Differentiation - Hidaka, Reiko; Miyazaki, Kazuko; Miyazaki, Masaki (Frontiers in Immunology, 2022)
Immune responses are primarily mediated by adaptive and innate immune cells. Adaptive immune cells, such as T and B cells, evoke antigen-specific responses through the recognition of specific antigens. This antigen-specific recognition relies on the V(D)J recombination of immunoglobulin (Ig) and T cell receptor (TCR) genes mediated by recombination-activating gene (Rag)1 and Rag2 (Rag1/2). In addition, T and B cells employ cell type-specific developmental pathways during their activation processes, and the regulation of these processes is strictly regulated by the transcription factor network. Among these factors, members of the basic helix-loop-helix (bHLH) transcription factor mammalian E protein family, including E12, E47, E2-2, and HEB, orchestrate multiple adaptive immune cell development, while their antagonists, Id proteins (Id1-4), function as negative regulators. It is well established that a majority of T and B cell developmental trajectories are regulated by the transcriptional balance between E and Id proteins (the E-Id axis). E2A is critically required not only for B cell but also for T cell lineage commitment, whereas Id2 and Id3 enforce the maintenance of naïve T cells and naïve regulatory T (Treg) cells. Here, we review the current knowledge of E- and Id-protein function in T cell lineage commitment and Treg cell differentiation.